A CASE REPORT OF MORVAN SYNDROME - Aytac, Emrah; Acar, Turkan (Literatura Medica, 2019)
Morvan syndrome is a rare disease characterized by peripheral nerve hyperexcitability, encephalopathy, dysautonomia and significant insomnia. The patient, who was included in the present study, was followed-up at our clinics for confusion, myokymia, hyperhidrosis, epileptic seizures, tachycardia, agitation, hypokalemia, and hyponatremia. The cranial MRI of the patient demonstrated hyperintensities at the T2 and FLAIR sections of the medial temporal lobe and insular lobes. Electromyography and neurotransmission examination results were concordant with peripheral nerve hyperreactivity. Contactin-associated protein-like 2 antibodies and leucine-rich glioma inactivated protein 1 antibodies were detected as positive. The patient was diagnosed with Morvan syndrome; intravenous immunoglobulin and corticosteroid treatment was started. Almost full remission was achieved. This very rare syndrome implies challenges in diagnosis and treatment; however, remission can be achieved during the follow-up. In addition, caution is needed in the long-term follow-up of these patients regarding the development of malignancies.
Keywords: Morvan syndrome; protein-like antibodies; LGI1-Ab; CASPR2-Ab